Palestinian strategies, guidelines, and challenges in the treatment and management of coronavirus disease-2019 (COVID-19) - Hatem A Hejaz (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Background: Coronavirus disease-2019 (COVID-19) outbreak is a global concern and the World Health Organization (WHO) has declared it as a Public Health Emergency of International Concern. The Palestinian Authority (PA) has quickly and effectively responded to the outbreak of COVID-19, using an internationally and nationally coordinated, to contain the spread of the virus within the borders. The PA approaches are containment and suppression, which is designed to protect the citizens from infection while also mitigating the stress on the health care system. The PA immediately declared a State of Emergency when the first cases in Palestine were diagnosed on 5 March 2020 and launched robust national containment measures to encourage the citizens to protect themselves and follow the guidance. Objectives: There is currently no vaccine or effective treatment for COVID-19, the treatment is either supportive and/ or the treatment of symptoms. Several strategies in the treatment of the disease were applied including medications. This review aims to summarize the different strategies, guidelines, challenges, and treatments used against COVID-19 worldwide and in Palestine. Materials and Methods: Different literature and guidelines among different databases were searched. Literature reviewing was conducted using the following search engines, Google Scholar, Medline, Pub Med, EMBASE, Web of Science, and Science Direct. Data also obtained from WHO and PA reports, and the published peer-reviewed articles of 2019-nCoV. The review focuses on the strategies, guidelines, therapeutics, challenges, and different approaches used in the treatment and management of the disease in Palestine and globally. Conclusion: The Palestinian Ministry of Health (MoH) strategies to end the COVID-19 pandemic were; slow and stop transmission; provide optimized care for patients; and minimize the impact of the epidemic on health systems, social services, and economic activity. Thus, proper management, right actions, and effective treatment of the disease should be considered to achieve these strategies. The biggest problem for PA to control and stop the outbreak of the disease is the different challenges which include; the Israeli military and economic control, uncontrol the borders, shortage of medical and financial resources, crowded cities and refugee camps, poverty, food insecurity, and the financial crisis. To date, there are no specific vaccines or medicines for COVID-19; and treatments are under investigation through clinical trials. However, an array of drugs approved for other indications, as well as multiple investigational agents, are being studied for the treatment of COVID-19; in several hundred clinical trials around the World. Treatment is essentially supportive and symptomatic.